Raising the Diversity of Ugi Reactions Through Selective Alkylations and Allylations of Ugi Adducts - Zidan, Alaa; El-Naggar, Abeer M.; Abd El-Sattar, Nour E. A.; Ali, Ali Khalil; El Kaïm, Laurent (Frontiers in Chemistry, 2019)
We report here selective Tsuji-Trost type allylation of Ugi adducts using a strategy based on the enhanced nucleophilicity of amide dianions. Ugi adducts derived from aromatic aldehydes were easily allylated at their peptidyl position with allyl acetate in the presence of palladium catalysts. These substitutions were compared to more classical transition metal free allylations using allyl bromides.